UPAYA GURU PPKN DALAM MENGATASI KENAKALAN SISWA DI DALAM KELAS MELALUI METODE PEMBELAJARAN KOOPERATIF PADA SEKOLAH MENENGAH PERTAMA NEGERI 5 BANDAR BARU KABUPATEN PIDIE JAYA - Nurdiana Nurdiana; Ery Wati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
Data collection techniques are using interviews, observation and documentation. The results of this study indicate that the Efforts of Citizenship Education Teachers in preventing student delinquency, through prevention in general and prevention in particular. Efforts to prevent the emergence of student delinquency in general are to know the difficulties and causes generally experienced by students and student development efforts. Meanwhile, efforts to prevent student delinquency in particular by providing guidance in the form of: self-adjustment and selforientation. Guidance is provided through an individual approach or directly on students who commit misbehavior so as not to commit further delinquency. The group approach is carried out on students in groups who commit delinquency so as not to repeat the delinquency so that it does not affect other students.Keywords: Efforts of Civics Teachers, Student Delinquency, SMP Negeri 5 Bandar Baru